Software integration in global software development: Challenges for GSD vendors. Issue 8 (21st April 2017) - Ilyas, Muhammad; Khan, Siffat Ullah
Abstract: Context: The advances in information and communication technologies have revolutionized the software development environment from local to global software development (GSD). This revolution also created challenges for vendor organizations. Vendors face challenges in integrating the components developed independently by GSD teams into a final working product. Objective: The objectives of the current study is to find out those critical barriers/challenges that hinder the integration process at any stage in the GSD environment for different types and size of projects. Methodology: For achieving the objectives we initially conducted a comprehensive systematic literature review (SLR). We searched 6 digital libraries and also followed the snowballing technique. The data was extracted from a total of 88 finally selected papers. Findings of the SLR study were then empirically validated through a questionnaire survey in GSD industry. A total of 96 experts from 22 different countries participated in the survey. Results: We have found a total of 16 barriers/challenges among which ten barriers are ranked as critical barriers/challenges. Some of the top ranked barriers are "lack of communication, " "lack of proper documentation, " "lack of compatibility, " and "architecture mismatch." The findings of our industrial survey are mostly coherent with the SLR findings. However, there is a difference in ranks of the various barriers/challenges across the 2 data sets (SLR and industrial survey). The identified challenges need to be properly addressed by software vendors to reduce the complexity of the integration process in GSD projects. Conclusion: We found that the severity of these barriers increases in large size projects. On the other hand, bespoke products are more affected by "lack of communication, " while off‐the‐shelf–based projects face integration problems due to "lack of compatibility, " "architecture mismatch, " and "wrong off the shelf product selection and customization".